Smart grid with cloud computing: Architecture, security issues and defense mechanism - Kaur, Kuljeet; Kumar, Neeraj (2014 9th International Conference on Industrial and Information Systems (ICIIS), 2014)
Smart Grid Network (SGN) is one of the innovative trends towards efficient and intelligent use of the conventional and non conventional resources of energy with respect to electric power generation, transmission and distribution. However, with the ever growing dependence and demand of modern life and industry on electricity, there arises a need of an integrated platform to manage these services in more efficient, reliable and transparent manner than ever before. In order to control the entire grid operations in a decentralized manner and analyze huge chunks of user specific data in an optimized manner, SGNs require dedicated resources. Thus, cloud computing platform is considered to be novel approach to fulfill these requirements and provide a more resilient and smarter approach to manage them. To primarily focus on these requirements, we present the basic architectural model to integrate SGNs with cloud computing technology. We also present a comprehensive survey on different security issues pertaining to this solution and the different ways to tackle them.